Midlatitude Oceanic Cloud and Precipitation Properties as Sampled by the ARM Eastern North Atlantic Observatory. Issue 8 (26th April 2019) - Giangrande, Scott E.; Wang, Die; Bartholomew, Mary Jane; Jensen, Michael P.; Mechem, David B.; Hardin, Joseph C.; Wood, Robert
Abstract: Marine low clouds are critical to the climate system because of their extensive coverage and associated controls on boundary layer dynamics and radiative energy balance. The primary foci for this study are marine low cloud observations over a heavily instrumented site on the Azores archipelago in the Eastern North Atlantic and their associated raindrop size distribution (DSD) properties, relative low cloud contributions to the precipitation, and additional sampling (instrument, environmental) considerations. The contribution from low clouds (e.g., cloud top < 4 km) to the overall precipitation over midlatitude oceans is poorly understood, in part because of the lack of coupled, high‐quality measurements of precipitation and low cloud properties. Cloud regime and precipitation breakdowns performed for a multiyear (2014–2017) record emphasize diurnal precipitation and raindrop size distribution characteristics for both low and deeper clouds, as well as differences between the two disdrometer types used. Results demonstrate that marine low clouds over this Eastern North Atlantic location account for a significant (45%) contribution to the total rainfall and exhibit a diurnal cycle in cloud (thickness, top, and base) and precipitation characteristics similar to satellite records. Additional controls on observed surface rainfall characteristics of low clouds allowed by the extended ground‐based facility data sets are also explored. From those analyses, it is suggested that the synoptic state exerts a significant control on low cloud and surface precipitation properties. Key Points: Low clouds over ENA account for a significant (45%) contribution to the total rainfall Low cloud diurnal cycle suggests a rainfall peak during the overnight hours and a secondary peak after local noon Synoptic state (sfc pressure and 850‐mb winds) exerts a significant control on low cloud properties including rainfall rate and drop size